Analisis Dukungan Sosial Pada Pasien Kanker Payudara Pasca Mastektomi di Kecamatan Semaka Kabupaten Tanggamus Lampung - Ika Nurmia; Lina Handayani (Jurnal Cakrawala Promkes, 2022)
Background: Social support in post-mastectomy breast cancer patients is still lacking, patients who do not get social support will feel inferior and isolate themselves. Objective: How is the social support provided by the immediate environment of cancer patients with mastectomy treatment? Methods: This research is a type of qualitative research that uses a case study design. Informants were taken using snowball sampling technique and found 4 key informants and 4 triangulated informants.Results: The appreciation support received by post-mastectomy breast cancer patients in Semaka District, Tanggamus Regency, Lampung is mostly words of encouragement, motivation and respect for patients. Material support received in the form of financial assistance from spouses and families, as well as assistance in providing fruits, food, drinks and purchasing medicines. Post-mastectomy breast cancer patients do not get informational support from their partners, friends and family. Conclusions: The emotional support received by the patient is affection, attention and sympathy, but not all patients get this support.